2014
DOI: 10.1902/jop.2014.130728
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Risk Indicators of Dentin Hypersensitivity in Adult and Elderly Populations From Porto Alegre, Brazil

Abstract: DH may be considered a concern in a Brazilian general population. Reduction of DH may be achieved by smoking cessation and periodontal health improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
47
1
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(62 citation statements)
references
References 30 publications
4
47
1
10
Order By: Relevance
“…In this study, the mean number of sensitive teeth peaked at 40–49 years, with similar values in the older age groups of 50–59 years and 60–69 years. This is comparable to other studies on DS with peak ages in the 5th and 6th decades . In this Trinidadian study, there was a tendency for an increased percentage of mean sensitive teeth with age, peaking at 60–69 years.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In this study, the mean number of sensitive teeth peaked at 40–49 years, with similar values in the older age groups of 50–59 years and 60–69 years. This is comparable to other studies on DS with peak ages in the 5th and 6th decades . In this Trinidadian study, there was a tendency for an increased percentage of mean sensitive teeth with age, peaking at 60–69 years.…”
Section: Discussionsupporting
confidence: 89%
“…Prevalence of DS amongst adults based on a literature review from 1964 to present (Table ) revealed a wide range in values from 1.3% to 73.0%. These differences in the prevalence may be related to the methodology of DS determination, with questionnaires probably overestimating the findings due to subjectivity in DS self‐reporting as opposed to more stringent measures of clinical determination.…”
Section: Introductionmentioning
confidence: 99%
“…GR is the main factor related to DH, which is characterized by a stimulated pain that is related to daily discomfort that can be reduced in some magnitude by periodontal plastic surgery. It was observed in this study that DH alone was not associated with OHRQoL.…”
Section: Discussionmentioning
confidence: 99%
“…When subjects with periodontal disease were studied, DH was associated with increased gingival recession (Rees & Addy , Costa et al. ) and radiographic bone loss (Fischer et al. ).…”
Section: Discussionmentioning
confidence: 99%